Ulucenie rezul'tatov poedinkov v edinoborstvach na osnove preimusestvennogo vypolnenija izljublennych atakujuscich priemov - Novikov, A. A.; Vangelov, Z.; Goranov, B.; Iskov, A. V.; Markin, P. S.; Chanbabaev, R. K. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The scientific-methodical literature on single combats and researches of authors was confirmed, that revealing and preferred performance in competitive duels of favorite grips has the great importance for the theory and practice of sports single combats.